Bharadwaj Aushadhalay - Dixit, Mukund; Sanjay, Verma (London : SAGE Publications Ltd, 2017)
This case provides an opportunity to identify and discuss issues in sustenance of an incumbents strategy in the changing environment. The context is the practice of Nadi Nidan (pulse diagnosis) and treatment of disorders based on this according to Ayurveda, the ancient system of Indian medicine. It describes the functioning of Bharadwaj Aushadhalay, an Ayurveda clinic run by Vaidyaji since 1955 and presents the history of the clinic, the process by which Vaidyaji learnt the practice of Nadi Nidan, the profile of the patients, the mode of treatment, restrictions imposed by Vaidyaji on the patients, their response and competitive pressures on the system. The case also provides a brief sketch of Ayurveda, its principles, currents trends in the education and research in Ayurveda, and recent advances in diagnostic tools and techniques. The case can be used in courses of Strategic Management in the module on Strategies for Sustainable Competitive Advantage and Knowledge Management.
Originally published: Dixit, M., & Sanjay, V. (2013). Bharadwaj Aushadhalay. BP0351. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bharadwaj Aushadhalay -- Case studies; Medicine, Ayurvedic -- History -- Case studies; Physical diagnosis -- Case studies; Medical care -- India -- Case studies